2001
DOI: 10.1097/00002820-200110000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Dying Children: A Comparative Study of Nurses??? Experiences in Greece and Hong Kong

Abstract: The purpose of this transcultural descriptive study was to explore the subjective experiences of 63 oncology and critical care nurses who provide care to dying children in Greece and Hong Kong. Semistructured interviews were conducted with 39 Greek and 24 Chinese nurses who described their experiences and responses to the dying process and death of children. The data were analyzed qualitatively and quantitatively, and nurses' responses were compared for their work setting (oncology versus critical care) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
1
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(110 citation statements)
references
References 24 publications
3
94
1
11
Order By: Relevance
“…This finding is consistent with previous studies in health care professionals [33][34][35][36][37][38][39][40][41] . Liben and colleagues previously reported that healthcare professionals often rely upon colleagues for support more than their family and friends 45 , whereas we found that GPs generally receive support from own family members and-to a lesser extent-their colleagues.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with previous studies in health care professionals [33][34][35][36][37][38][39][40][41] . Liben and colleagues previously reported that healthcare professionals often rely upon colleagues for support more than their family and friends 45 , whereas we found that GPs generally receive support from own family members and-to a lesser extent-their colleagues.…”
supporting
confidence: 93%
“…Several studies reported how providing pediatric palliative care affects health care professionals [33][34][35][36][37][38][39][40][41] . Thus, we hypothesized that providing home-based palliative care to a child with incurable cancer is likely a challenging task for many GPs.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Um significado marcado pelo crescimento, pela paz, luz, força interior, beleza, por sentimentos de amor e ampliação da consciência de si e do mundo. Devemos viver intensamente até o momento da morte, pois ao separarmos o processo do morrer da vida deixamos de viver antes da morte (20) .…”
Section: A Morte Em Diferentes Fases Da Vidaunclassified
“…Situación que se manifiesta por problemas de salud físico, psico emocionales y mentales, afectando a la persona en su totalidad, lo que puede verse asociado a depresión, ansiedad, desmotivación, baja autoestima, tendencia al aislamiento, entre otros. Esta situación se observa con mayor frecuencia en funcionarios de unidades de alta complejidad como son oncología y cuidados intensivos pediátricos 14,15 , especialmente en funcionarios con menor formación 6,16 . En ambas unidades se atiende a niños con cáncer, que requiere manejo de tratamientos prolongados, intensivos y de alta toxicidad, lo que lleva a una creciente demanda asistencial 17 , sumándose a esto factores organizacionales tales como el cansancio por carencia de personal, déficit comunicacional, toma de decisiones subrogadas, conflictos de rol, sistema de turnos complejos, incompatibilidad entre las vida laboral y personal, y menor tiempo de descanso 18 .…”
Section: Introductionunclassified